Modulation of Bambusuril Anion Affinity in Water - Havel, Vaclav; Babiak, Michal; Sindelar, Vladimir (Chemistry (Weinheim an der Bergstrasse, Germany), 2017)
Neutral and negatively charged anion receptors functioning in pure water are rare in supramolecular chemistry. Moreover, studies on adjusting the affinity of such receptors toward anions in water are absent from the literature. Two new bambusurils, 1 a and 2 a, were prepared to demonstrate that the affinity of bambusurils towards anions can be altered by the length of carboxyalkyl groups attached to the macrocycles. The stability of the bambusuril complexes was further controlled by the pH value. The crystal structure of bambusuril 1 a was described, in which two carboxyalkyl arms fold into the macrocycle cavity, thus forming the intramolecular self-inclusion complex.
Keywords: macrocycles; anion recognition; self-assembly; supramolecular chemistry; bambusurils